Prevalence of hypertension in asymptomatic children without risk factors (Annals of Medical Research, 2025)
Aim: This two-year a cross-sectional study investigated the prevalence of hypertension in asymptomatic children (ages 3-18) without known risk factors, hypothesizing that increased screen time and sedentary lifestyles contribute to rising rates. The cross-sectional study, conducted from January 1, 2021, to January 1, 2022, included children attending the General Pediatrics clinic at İnönü University Faculty of Medicine.Materials and Methods: Of the 468 participants, 10.3% had prehypertension, 15.2% had stage 1 hypertension, and 7.1% had stage 2 hypertension, resulting in a total hypertension prevalence of 32.5%. The hypertensive group had a significantly higher BMI (19.3±5.4 vs. 17.6±3.6, p
Keywords: Hypertension; Coronary artery disease; Obesity; Body mass index